How do food safety technical working groups within a One Health framework work? Experiences from Vietnam and Ethiopia - Lam, Steven; Sinh Dang-Xuan; Bekele, Meseret; Amenu, Kebede; Alonso, Silvia; Unger, Fred; Hung Nguyen-Viet (Springer, 2024)
Background: Persistent challenges of fragmented, food safety management in low- and middle-income countries underscore the need for more robustly coordinated mechanisms. National food safety technical working groups, operating under a One Health framework, offer potential in streamlining coordination efforts to effectively address these challenges. However, more clarity regarding their formation and functioning is important for understanding how to best establish and support such groups. The aim of this study is to systematically document the development process of established groups in Vietnam and Ethiopia.